Social Impact of CRM on Customer Engagement and User Loyalty to Services by.U - Ali Ibrahim; Lukmanul Hakim; Alif Mustaqim; Naberi Oktaria; Tasya Permata Listi; Yunita Faujiyah (Universitas Medan Area, 2022)
The development of digitalization continues to grow very rapidly, making companies continue to innovate such as telecommunications technology companies. by.U is an innovation from a telecommunications technology company that has the advantage of being the first all-digital provider in Indonesia. In the by.U service, users can be flexible in determining quota filling according to the desired request. The purpose of this study was to find out how much influence the Social CRM activities carried out by.U had on increasing customer engagement and user loyalty. This research was conducted on the service by.U. Data were analyzed using SmartPLS with a sample of 30 people. The research method is a quantitative approach with path analysis using SmartPLS Version 3. The results of the research are that there are 2 hypotheses that have a significant effect, namely: (1) Social Customer Relationship Management has a significant influence on Loyalty; (2) Social Customer Relationship Management has a significant influence on customers. While the two hypotheses are not significant, namely: (1) Social Customer Relationship Management has a significant influence on Loyalty in Intervening Customer Engagement; (2) Customer Engagement has a significant effect on Loyalty